Somatosensory scaffolding structures - Jeske, Nathaniel A. (Frontiers in Molecular Neuroscience, 2012)
Dynamic changes in somatosensory perception occur as a result of multiple signaling events. In many instances, over-activation of sensory receptors results in the desensitization and subsequent increased threshold for activation of receptors. In other cases, receptor sensitization can occur following tissue injury and/or inflammation. In both cases, signaling mechanisms that control alterations in receptor activities can significantly affect organism response to sensory stimuli, including thermal, mechanical, and chemical. Due to the homeostatic nature of somatosensory recognition, dynamic changes in receptor response can negatively affect an individual’s way of life, as well as alert individuals to tissue damage. Here, we will focus on scaffolding structures that regulate somatosensory neuronal excitability.